Trends in Undergraduate Soil Science Education at Selected Universities in the USA from 2009 to 2013. Issue 2 (22nd February 2018) - Brevik, Eric C.; Vaughan, Karen L.; Parikh, Sanjai J.; Dolliver, Holly; Lindbo, David; Steffan, Joshua J.; Weindorf, David C.; McDaniel, Paul; Mbila, Monday; Edinger-Marshall, Susan
Abstract : Core Ideas: Enrollment increased in most soil science courses from 2009 to 2013. Students from many different majors took soil science coursework. Total female enrollment increased, but the percentage of female students decreased. Soil judging participation remained consistent. Student to faculty ratio went up between 2009 and 2013. Data were collected from 10 universities in the United States on declared academic majors and gender of students enrolled in seven different soil science courses over a 5‐yr period. Combined trends for all courses and trends for each individual course were evaluated. Data were also collected on the number of students participating in soil judging as well as tenure track and non‐tenure track full time equivalent (FTE) soil science faculty positions. Environmental science, crop science/horticulture/agronomy, and other agricultural students enrolled in soil science courses in the greatest numbers. Environmental science and engineering students showed rapid increases in enrollment, while crop science/horticulture/agronomy and soil science student enrollment declined. Soil physics was the only class where declared soil science students were the single largest enrolled group. Soil judging numbers were consistent, while FTE faculty showed a slight decline. Students from many different academic majors took soil science courses at the universities investigated, and the most common majors in these courses depended on the course and the material it addressed. Overall student enrollment increased in all subject areas investigated except soil physics. While the results from this study are somewhat mixed, the overall growth in student enrollment in soil science courses at the investigated universities, as well as the broad range of majors enrolled in soil science coursework, indicate an upward trajectory in soil science education at these universities.